Net energy and protein requirements for pregnancy differ between goats and sheep - Harter, C. J. [UNESP]; Ellis, J. L.; France, J.; Resende, K. T. [UNESP]; Teixeira, I. A. M. A. [UNESP] (Amer Soc Animal Science, 2016)
Current feeding systems for goats estimate the energy and protein requirements for pregnancy using data from sheep. The objective of this study was to predict the NE and net protein requirements for pregnancy in goats carrying single and twin fetuses and to compare these requirements with those of sheep. Data were compiled from 2 studies with dairy goats and 3 studies with sheep. These studies measured the energy content (EC) and protein content (PC) of the gravid uterus and of the mammary gland using the comparative slaughter technique. The current study was performed as a meta-analysis using an exponential model, comparing species (sheep versus goats) and litter size (single versus twin) from 50 to 140 d of pregnancy. Total EC and total PC in the gravid uterus were similar in goats and sheep carrying a single fetus. Energy and protein contents of the gravid uterus of sheep carrying twins were, on average, 29% greater than that of goats with twins from 80 to 140 d of pregnancy. During pregnancy, EC and PC of the mammary gland in goats carrying singles and twins were, on average, greater than those of sheep by 9 and 24%, respectively, for EC and by 25% for PC for both litter sizes. In conclusion, the gravid uterus and the mammary gland of goats and sheep require different amounts of energy and protein. Sheep carrying twins have the greatest daily NE and net protein requirements for pregnancy followed by goats carrying twins and both species carrying a single fetus. Therefore, it is inappropriate to adopt data from sheep to predict the net pregnancy requirements of goats, and the results found in this study could be relevant to the nutritional management of dairy goats.
Keywords: adnexa of uterus; conceptus; does; ewes; fetuses; gestation